PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THREE STAY ONE STRAY UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA - Ismi Ardayani (Madah: Jurnal Bahasa dan Sastra, 2017)
The problem in this research is found in the subjects of Indonesian language that is the level of students' writing scientific is still low. The low scientific writing skill of the students can be seen from the students’ composing sentences that have not used correct arrangement patterns in describing an essay yet. To overcome the low skill of writing scientific essay, the researcher proposed solution by using cooperative learning model Three Stay One Stray. The formulation of the problem in this research is whether the application of Three Stay One Stray learning model can improve student learning outcomes of grade VII.2 SMPN 3 Pekanbaru in 2016/2017. This study aims to determine whether the application of learning model Three Stay One Stray can improve student learning outcomes of grade VII.2 SMPN 3 Pekanbaru Academic Year 2016/2017. This classroom action research is conducted for 2 months, from September toNovember 2016. This classroom action research is conducted in 2 cycles, with 6 meetings. Based on the results of the study, it can be concluded that the implementation of learning model Three Stay One Stray can improve student learning outcomes of grade VII.2 SMPN 3 Pekanbaru in 2016/2017. It can be seen from the improvement of learning outcomes of Indonesian language subject before and after the implementation of cooperative learning model Three Stay One Stray in cycle I and cycle II.